2005
DOI: 10.1002/qsar.200430917
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Elucidation of DPPH Radical-Scavenging Activity Difference of Antioxidant Xanthones

Abstract: As naturally occurring polyphenols, xanthones are rather active in scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. By means of quantum chemical calculation, we reveal that the activity difference of xanthones can be elucidated by their different O À H bond dissociation enthalpies (BDEs) and can be further explained in terms of electronic effect and intramolecular hydrogen bond effect of substituents. The unique structure of xanthones enables them to be promising antioxidants with advantages of rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…On the other hand in 9, the electron donating effect induced by the O-group may facilitate such a process. The above findings are in accordance with theoretical data presented for a natural xanthone, scutellarin and baicalein with similar substituents with the above mentioned aurones (Ji, Tang, & Zhang, 2005). Regarding aurones 3-8 bearing one O-H group in ring A the contribution of the respective group in activity of compounds should be negligible as in 3, 5, 7 and 8 the BDE values are comparable or higher to that of simple phenol.…”
Section: Hydrogen Atom Donationsupporting
confidence: 94%
“…On the other hand in 9, the electron donating effect induced by the O-group may facilitate such a process. The above findings are in accordance with theoretical data presented for a natural xanthone, scutellarin and baicalein with similar substituents with the above mentioned aurones (Ji, Tang, & Zhang, 2005). Regarding aurones 3-8 bearing one O-H group in ring A the contribution of the respective group in activity of compounds should be negligible as in 3, 5, 7 and 8 the BDE values are comparable or higher to that of simple phenol.…”
Section: Hydrogen Atom Donationsupporting
confidence: 94%
“…Ji et al, 2005;Nenadis et al, 2003;Zhang et al, 2003), a computational study was also carried out. To our knowledge, such a study has not been reported so far.…”
Section: Theoretical Studymentioning
confidence: 99%
“…Ji, Tang, & Zhang, 2005;Nenadis, Zhang, & Tsimidou, 2003;Zhang, Wang, & Sun, 2003), a computational study was also employed for the first time to complement experimental findings. Computations were carried out by means of a combined DFT/AM1 method, which provides economy and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…1). They were separated into the following groups: group A: hydroxy cinnamic acids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15); group B: standard antioxidants (16)(17)(18); group C: flavonoids and related compounds (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33); group D: hydroxy chalcones (34)(35)(36)(37)(38); group E: dihydroxy coumarins (39)(40)(41)(42); and group F: binary mixtures of two antioxidants (43)(44)(45)(46)(47)(48)(49)(50). Correlations between ...…”
Section: Introductionmentioning
confidence: 99%